Aromatase inhibitor treatment limits progression of peritoneal endometriosis in baboons - Langoi, David; Pavone, Mary Ellen; Gurates, Bilgin; Chai, Daniel; Fazleabas, Asgerally; Bulun, Serdar E. (Elsevier Science Inc, 2013)
Objective: To determine the effect of inhibiting aromatase activity on endometrial lesion growth and aromatase expression in a baboon model of induced endometriosis. Design: Prospective study. Setting: Primate research institute. Animal(s): Sixteen olive baboons. Intervention(s): Sixteen olive baboons with induced endometriosis were examined with laparoscopy 10 months after disease inoculation. Animals in group 1 (n = 10) were treated with 1.25 mg/d of the aromatase inhibitor (AI) letrozole, and animals in group 2 (n = 6) were given a placebo for a total of 6 months. Main Outcome Measure(s): Total number of endometriotic lesions, morphology, and volume of lesions, as well as semiquantitative reverse transcription-polymerase chain reaction and quantitative polymerase chain reaction for levels of aromatase cytochrome messenger RNA were measured. Ovarian volumes were evaluated before treatment initiation and every 2 months during the study. Result(s): Treatment of group 1 animals with an AI significantly decreased lesion volume from baseline measurements, whereas the placebo-treated animals showed an increase in lesion volume. Aromatase messenger RNA levels in lesions in the AI-treated animals were significantly lower compared with the placebo-treated animals. Ovarian volumes were significantly increased at 6 months of AI treatment compared with pretreatment volumes. Conclusion(s): These findings suggest that suppression of aromatase cytochrome P450 may inhibit the in vivo growth of endometriotic lesions in baboons. (Fertil Steril (R) 2013;99:656-62. (C) 2013 by American Society for Reproductive Medicine.)
Keywords: Endometriosis; aromatase inhibitors; baboon model; laparoscopy